Hubungan Antara Self-Efficacy dengan Prokrastinasi Akademik pada Mahasiswa Keperawatan dalam Menyusun Skripsi - Carresa Anja Safara; Retno Isroviatiningrum; Muh Abdurrouf (Journal of Medical Practice and Research, 2025)
This study investigates the role of self-efficacy in academic procrastination among nursing students during the thesis-writing process, considering that the thesis is a primary graduation requirement that is frequently hindered by postponement behaviors. A quantitative design with a cross-sectional approach was employed involving 140 active nursing students from the 2022 cohort at Sultan Agung Islamic University Semarang, selected through simple random sampling. Data were collected using the General Self-Efficacy Scale and the Academic Procrastination Scale, and subsequently analyzed using univariate and bivariate techniques with the Spearman Rank correlation test. With a p-value of 0.000 and a correlation coefficient of r = -0.815, the statistical test established a strong and significant relationship between academic procrastination and self-efficacy. This inverse correlation indicates that students' procrastination decreased as their self-efficacy increased. This study emphasizes the importance of students' beliefs in their own abilities to succeed academically. Therefore, interventions aimed at enhancing self-efficacy through academic mentoring, skills training, and psychological support should be developed to reduce procrastination and promote timely and optimal thesis completion.